Study of Monitoring Water Quality as Impact of Steam Power Plant (SPP) 3 x 10 MW Tanjung Enim Banko Operational Activities - Azis Koswara; Eddy Ibrahim; Novia Novia (Program Pascasarjana Universitas Sriwijaya, 2021)
The construction of power plants is very necessary to anticipate the crisis of electricity resources and always increases every year. Tanjung Enim city has Steam Power Plant (SPP), one of them is Banko SPP which has 3 x 10 MW capacity. It was built to meet the demand for society electrical energy. The existence of this SPP construction can cause environmental degradation such as a decrease in water quality that does not meet environmental quality standards. The decline in environmental quality can also have a direct impact on the community around the Tanjung Enim SPP location. This is due to the existence of SPP operational activities that can produce liquid waste such as boiler blowdown, airheater blowdown, cooling system and domestic waste waterfrom the manufacturing process. This research study aims to analyze water quality around Banko SPP based on the physical and chemical parameters by testing in the laboratory. The approach employed in this study was an experimental method that included laboratory sample and testing. The water quality pollution index (PI) which refers to the Ministerial Decree No. 115/2003 (Environmental Decree) was used to analyze the result of laboratory testing. The water quality samples examined in this study were wastewater treatment plant (WWTP) outlet, river water, and groundwater nearest to the SPP's location. The phenol and chlorine parameters exceeded the quality requirements referred to in the South Sumatra Governor Regulation No. 16 of 2005, according to the findings of laboratory testing of river water samples. The mercury (Hg) parameter in the WWTP outlet samples surpassed the South Sumatra Governor Regulation No. 16 of 2005 quality criteria. Meanwhile, the manganese (Mn) parameter in groundwater samples surpasses the quality requirement established by the Government of South Sumatra Regulation No. 82/ 2001 as Class I clean water quality criteria. The water quality pollution index (PI) method achieves a score of 1.52 with the category of Lightly Polluted. Based on these findings, it can be concluded that the influence of SPP Banko's operations on water contamination is minor.